Yugto city rehabilitation complex of Manila in a post-biowarfare setting - Rance, Ma. Chealsy Louise F.; Luna, Markel Cesar A. (Quezon City College of Architecture, University of the Philippines Diliman, 2021)
Warfare has been engraved in human history since time immemorial. Wars have changed the course of the world many times in the past. Even in the present, there are wars happening around the world. With the increasing tension between and within nations from the arms race, terrorism, territorial conflicts, and others, it is difficult to ensure a future without warfare. War has left cities in rumbles, forced people to migrate from their homes, and turned communities to ghost towns. The world has faced several conflicts but one of the most destructive wars of the future deducted is a biological warfare. Biowarfare can transcend international regulations, hiding behind the shadows of "natural" phenomena through the spread of diseases. I believe that the aftermath of Bio war is more dreadful than the war itself. The project aims to provide an architectural solution to the problem, ghost cities as a result of biological warfare. The project is entitled "Yugto : a city rehabilitation complex of Manila in a post-biowarfare setting". Yugto, a Filipino word meaning "a fundamental transition or development of a story or phenomenon" symbolizes the state of recovery of communities after the chaos of war. The project features temporary and transitional spaces, designed for disassembly using pre-fabricated and modular systems, to bring people back to the city of Manila, helping the community revive the city's activities by providing temporary home and community spaces, dealing with the war-affected facets of society, the environment, the individual, and the community.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Community development -- Manila; Urban development -- Manila